Interest Rate Effects on Output: Evidence from a GDP Forecasting Model for South Africa. - Aron, J; Muellbauer, J (2002)
Forecasting models for output are presented to throw light on monetary transmission. Recent research finds multistep forecasting superior to recursive forecasting from a VAR model when structural breaks are present; there are important political and policy regime breaks in South Africa. The equilibrium correction models have a four-quarter ahead forecast horizon, appropriate for measuring interest rate effects. A stochastic trend measures underlying shifts in productivity and other supply side trends. The inclusion of important monetary policy regime shifts, which altered the output response to interest rates, and control for other structural changes (e.g. trade liberalization), address the Lucas critique in forecasting output growth. There are important and persistent effects of high real interest rates, which significantly constrained growth in the 1990s, and significant potential growth benefits from fiscal discipline. South African growth appears to have become more responsive to the exchange rate with increasing trade openness in the 1990s.